Occurrence of Aflatoxin M1 over Three Years in Raw Milk from Croatia: Exposure Assessment and Risk Characterization in Consumers of Different Ages and Genders - Nina Bilandžić; Ines Varga; Bruno Čalopek; Božica Solomun Kolanović; Ivana Varenina; Maja Đokić; Marija Sedak; Luka Cvetnić; Damir Pavliček; Ana Končurat (Foods, 2025)
In this study, the frequency of aflatoxin M1 (AFM1) occurrence in raw milk was investigated across different seasons over a three-year period from 2022 to 2024 in Croatia. Risk assessment was conducted using estimated daily intake (EDI), hazard index (HI), and margin of exposure (MOE) for various age groups and both genders. The frequency of AFM1 detection above the maximum level (ML) ranged from 1.60% to 15.1%. The average incidence of AFM1 exceeding the ML was 5.67%, with the highest incidence recorded in autumn 2024. AFM1 levels within the limit of detection (LOD) and ML were found in 13% of the samples. The average mean value of AFM1 over the three-year period was 19.2 ng/kg. The highest mean AFM1 EDI values were determined for toddlers (0.61–0.67 ng/kg bw/day) and children (0.41–0.43 ng/kg bw/day). The lowest EDI values were observed in elderly females and males (0.058–0.074 ng/kg bw/day). The EDI values for females and males were slightly different. The risk assessment, based on the HI and MOE, indicated that toddlers and children are at the highest risk of exposure to AFM1, which raises significant health concerns. Additionally, consumers of large quantities of milk face a high risk of exposure, particularly during the spring and autumn seasons. For adults and the elderly, milk consumption does not pose a serious health risk.